Anti-Wrinkle Efficacy of Edible Bird’s Nest Extract: A Randomized, Double-Blind, Placebo-Controlled, Comparative Study - Kim, Hyung Mook; Lee, Yong Moon; Kim, Ee Hwa; Eun, Sang Won; Sung, Hyun Kyung; Ko, Heung; Youn, Sang Jun; Choi, Yong; Yamada, Wakana; Shin, Seon Mi (Frontiers in Pharmacology, 2022)
This study aimed to evaluate skin health’s functional improvement, such as wrinkles, elasticity, moisture, and whitening, and safety following the consumption of “edible bird’s nest extract” for 12 weeks by women. This single-center, double-blinded, parallel-group, placebo-controlled study included women aged 40–60 years. Our primary purpose was to assess improvement in skin wrinkles, elasticity, and moisture after 12 weeks using an SV700, cutometer, and corneometer, respectively, compared to baseline measurements. Our secondary purpose was to evaluate skin wrinkle, elasticity, and moisture changes at 4 and 8 weeks from baseline using the aforementioned equipment, and measure transdermal water loss and melanin and erythema indexes using a tewameter and mexameter, respectively. Experts performed the visual evaluation of skin wrinkles at 4, 8, and 12 weeks from baseline. The participants were randomly allocated in a 1:1 ratio into the edible bird’s nest extract or the placebo group with 43 participants each, where they consumed 100 mg of the extract or placebo, respectively, daily for 12 weeks. The outcomes were measured at every visit. In this study, upon comparing changes in the skin elasticity value between the two intake groups at 12 weeks of ingestion, skin elasticity in the edible bird’s nest extract group decreased significantly compared with that in the placebo group. Adverse reactions were absent in both groups. In the case of laboratory test results, changes before and after the ingestion of the extract were within the normal range, thus indicating no clinically significant difference. The edible bird’s nest extract was effective in improving skin wrinkles. Moreover, it is beneficial for skin health and can be used as a skin nutritional supplement. Compared with the placebo, the edible bird’s nest extract was identified as safe. Clinical Trial Registration:<ext-link ext-link-type="uri" xlink:href="https://cris.nih.go.kr/cris/search/detailSearch.do?search_lang=E&search_page=M&pageSize=10&page=undefined&seq=21007&status=5&seq_group=20330" xmlns:xlink="http://www.w3.org/1999/xlink">https://cris.nih.go.kr/cris/search/detailSearch.do?search_lang=E&search_page=M&pageSize=10&page=undefined&seq=21007&status=5&seq_group=20330, identifier KCT0006558.